Gene mutation landscape of a rare patient with acute megakaryoblastic leukemia after treatment of intracranial germ cell tumor - Wang, Li-Xin; Liao, Wei-Jie; Jiang, Yu-Hua; Chen, Chao; Lu, Wang-Sheng; Yin, Feng; Ning, Hao-Yong (Frontiers in Oncology, 2023)
Germ cell tumors patients are first reported to suffer hematologic malignancies 37 years ago. Subsequently, relevant reports increased year by year, and most cases are mediastinal germ cell tumors. The theories for explaining the phenomenon include the same progenitor cells origin, effects of treatment and independent development. Till to now, there is no widely accepted explanation. Cases with acute megakaryoblastic leukemia and intracranial germ cell tumors are rarely reported before and the association is far less known. We here report a patient with acute megakaryoblastic leukemia after treatment of intracranial germ cell tumor. Whole exome sequencing and gene mutation analysis revealed that the two tumors shared the same mutation genes and mutation sites, suggesting they belong to the same origin and begin to differentiate in the later stage. Our finding first supported the theory that acute megakaryoblastic leukemia and intracranial germ cell tumors share the same progenitor cells.